Factors Affecting Financial Decision Making: The Women lecture’s Perspective - Y. K. Arumsari; . Surachman; . Sumiati; . Andarwati (Финансы: теория и практика, 2024)
Research on women’s financial decision-making involves a great deal of behavior and financial research. Due to the complexity of the phenomenon and the fact that it encompasses various aspects of life, making a deep-seated decision necessitates consideration of both financial and cognitive factors. A woman, as a wife, plays a vital role in the household, especially in terms of financial decisions.   The purpose of the study is to assess a variety of determinant-taking decisions lecturer finance woman, Dpk LLDikti Region VII, Indonesia.   It evaluates connection intelligence fluid (FI), which consists of dimensions number intelligence (FI NI), verbal comprehension (FI VU), perception speed (FI PS), inductive reasoning (FI IR), and deductive reasoning (FI DR), as well as literacy finance (FL) with making financial decisions (FDM). It employs a quantitative statistical method to examine the relationship between specified variables. Using smartPLS 4, primary data from a structured questionnaire utilizing a 5-point Likert scale were analyzed using a partial least squares-structural equation modeling approach. FI NI; FI VU; FI PS; FI IR; and FI DR exhibited a positive and statistically significant correlation with FI, as indicated by the results. This also demonstrates that FI and FL have a positive and substantial relationship. The results also demonstrate that FI and FL have a positive and statistically significant relationship with FDM. Successful FDM requires FI (FI VU; FI PS; FI IR; FI DR) and FL to optimally execute a systematic and logical decision-making process.